A framework for assessing project vulnerability to crises. Issue 4 (22nd March 2019) - Wang, Aimin
Abstract : Purpose: The purpose of this paper is to propose a framework for assessing the vulnerability of projects to crises. The study seeks to clarify the cascade effects of disruptions leading to project crises and to improve project robustness against crises from a systems perspective. Design/methodology/approach: A framework for assessing project vulnerability to crises is developed using complex network theory. The framework includes network representation of project systems, analyzing project network topology, simulating the cascade of unexpected disruptions and assessing project vulnerability. Use of the framework is then illustrated by applying it to a case study of a construction project. Findings: Project network topology plays a critical role in resisting crises. By increasing the resilience of the critical tasks and adjusting the structure of a project, the complexity and vulnerability of the project can be reduced, which in turn decreases the occurrence of crises. Research limitations/implications: The proposed framework is used in a case study. Further studies of its application to projects in diverse industries would be beneficial to enhance the robustness of the results. Practical implications: Project crises can threaten the survival of a project and endanger the organization's security. The proposed framework helps prevent and mitigate project crises by protecting critical tasks and blocking the diffusion path from a systems perspective. Originality/value: This paper presents a novel framework based on complex network theory to assess project vulnerability, which provides a systemic understanding of the cascade of disruptions that lead to project crises.